Choices, Beliefs, and Infectious Disease Dynamics - M. Christopher Auld (Queen's University, Department of Economics, 1996)
This paper develops a dynamic model of behavioural response to the risk of infectious disease. People respond to increased risk of infection by either making marginal adjustments in risky behaviour or by moving to a corner solution where perceived risk is zero. Individuals most prone to high-risk activity will tend to reduce activity less than low-risk people; very high risk people may exhibit "fatalism" and increase risky behaviour as the risk of becoming infected rises. Beliefs about the future course of the epidemic affect current behaviour even when utility is additively separable: pessimistic beliefs induce more risky behaviour. Simulations contrast the disease dynamics generated under these behaviours with those of standard epidemiological models and examine policy issues.
Keywords: I1; D8; 330; epidemiology; AIDS; uncertainty